On the modelling of low to medium velocity impact onto woven composite materials with a 2D semi-continuous approach. (15th December 2015) - Pascal, F.; Navarro, P.; Marguet, S.; Ferrero, J-F.
Abstract: An explicit finite element modelling of the 5-harness satin woven composite material is proposed in this paper. It is based on the semi-continuous approach which consists in separating fibre and matrix mechanical behaviours. The bundles are modelled with rod elements and a specific damageable shell element is used to stabilize this truss structure. As the woven pattern geometry plays a key role in damage initiation and propagation, a modification has been made in the failure strain of the rods located at the crimp regions where warp and weft yarns cross each other. The method has been implemented into the explicit finite element code RADIOSS and is computationally efficient to model low to medium velocity impact (1–200 m/s) at the structure scale. The modelling strategy is validated by representing a drop weight test and an oblique impact test and provides good prediction of impact force history and damage size and location.